Developing listening skills for high school students through songs: An empirical study - N H, Thang; N H, The; T T, Du (International Journal of Social Sciences and English Literature, 2024)
The current study concentrates on listening, one of the four basic language skills. According to the Common European Framework of Reference for Languages, listening is frequently overlooked, and students almost tend to struggle to learn through it. This study’s objective is to evaluate the effects of songs on students’ listening skills and motivation. The participants included two groups of 11th grade students from a high school in Binh Duong province of Viet Nam, who learned English as a foreign language. Questionnaires and interviews were utilized to acquire both quantitative and qualitative data. A pre-test and a post-test were also prepared to assess both how far the students progressed after implementing the study project and their motivation in learning English through songs. At the end of the treatment, the average post-test score was greater than the pre-test score within experimental group. Research results indicate that music and songs may not only be entertaining, but also give students several benefits, a specially in developing their listening skills. Students’ motivation in their language learning in general and in learning listening skills also increased considerably.